Multimodal prehabilitation is an effective strategy to reduce postoperative complications and improve physical function and anxiety in patients with colorectal cancer undergoing elective surgery: a systematic review and network meta-analysis - Li, Na; Liu, Xiaoli; Wang, Yanping; Song, Ruimei; Xie, Xufeng (Frontiers in Medicine, 2025)
BackgroundPreoperative prehabilitation represents a viable approach to improve postoperative recovery and quality of life in colorectal cancer (CRC) patients, though debates persist regarding the efficacy of specific prehabilitation modalities.ObjectiveThis study aims to compare and rank prehabilitation strategies for enhancing postoperative outcomes in CRC patients through a network meta-analysis, identifying the optimal preoperative prehabilitation method.MethodsWe included randomized controlled trials (RCTs) assessing four prehabilitation strategies in CRC patients. Outcome measures focused on postoperative complications, hospital stay duration, 6-min walk test, and states of anxiety and depression. The effect sizes for dichotomous outcomes were measured by odds ratios (OR), and for continuous outcomes by mean differences (MD) or standardized mean differences (SMD), with 95% credible intervals (CrIs).ResultsOur analysis included 27 RCTs involving 2,946 CRC patients. NMA results indicated that, compared to the control group (CON), only the multimodal (Mul) approach significantly reduced postoperative complications (OR: 0.47, 95%CrI: 0.26–0.85) and hospitalization time (MD: −1.17, 95CrI: −1.77 to −0.57). Moreover, Mul was the only strategy that improved pre-surgical 6-min walk test results (MD: 27.22, 95CrI: 12.71–41.73) and anxiety levels (SMD: −0.69, 95CrI: −1.34 to −0.04), with sustained improvements in the 6-min walk test observed up to 4 weeks post-surgery (MD: 19.22, 95CrI: 5.94–32.50).ConclusionThe Mul prehabilitation program is the effective strategy for improving surgical outcomes in CRC patients. This comprehensive approach not only aids in reducing postoperative complications and shortening hospital stays but also enhances physical and psychological readiness before surgery.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024514661.